PERAN GURU PENDIDIKAN AGAMA ISLAM SEBAGAI MODEL TELADAN DALAM MENGINTERNALISASIKAN NILAI AKHLAKUL KARIMAH - Nia Nia (Tarbiya Islamica, 2013)
This research uses a qualitative approach and uses a descriptive type of research. Data collection techniques using interviews, observation and documentation. The data analysis technique used is the data reduction stage, data presentation and the conclusion stage. The data validity techniques used were triangulation and member check. The results of this study indicate that: 1) The role of Islamic religious education teachers as models and role models in internalizing the moral values ​​of speaking aspects of students in class XII TKR-B SMK Subur Insani Sambas, familiarize and exemplify students to say the soft and gentle. good to hear both in class and outside the class, exemplifying to students how to say good words, talking never harshly and avoiding loud words, when calling students by name and avoiding calling with your words or you, Greeting students in full 2) The role of the Islamic religious education teacher as a model and role model in internalizing the moral values ​​of dressing in students in class XII TKR-B SMK Subur Insani Sambas, dressed neatly ironed when coming to school and wearing a blazer and usually also wearing a plain shirt , dressed neat and polite and close aurat. 3) The role of Islamic religious education teachers as models and role models in internalizing the values ​​of akhlakul karimah behavior in students in class XII TKR-B SMK Subur Insani Sambas, behaving fairly to students, exemplifying students by coming to school earlier than time which has been determined from the school, when entering class says greetings, does not act arrogantly and does not demean others, exemplifies throwing garbage in its place.